Diastolic Cardiac Function Improvement by Liraglutide Is Mainly Body Weight Reduction Dependent but Independently Contributes to B-Type Natriuretic Peptide Reduction in Patients with Type 2 Diabetes with Preserved Ejection Fraction. (28th March 2021) - Yagi, Kunimasa; Imamura, Teruhiko; Tada, Hayato; Chujo, Daisuke; Liu, Jianhui; Shima, Yuuki; Ohbatake, Azusa; Miyamoto, Yukiko; Okazaki, Satoko; Ito, Naoko; Nakano, Kaoru; Shikata, Masataka; et al.
Abstract : Objectives . A single-arm prospective study was conducted among Japanese patients with type 2 diabetes having preserved ejection fraction. The aim was to investigate (1) whether liraglutide therapy could improve B-type natriuretic peptide (BNP) levels and diastolic cardiac function assessed by the E -wave to E ′ ratio (E / E ′ ) using transthoracic echocardiography (TTE), and (2) whether E / E ′ contributed to BNP improvement independent of bodyweight reduction (UMIN000005565 ). Methods . Patients with type 2 diabetes and left   ventricular   ejection   fraction   LVEF ≥ 40 % without heart failure symptoms were enrolled, and daily injection with liraglutide (0.9 mg) was introduced. Cardiac functions were assessed by TTE before and after 26 weeks of liraglutide treatment. Diastolic cardiac function was defined as septal E / E ′ ≥ 13.0 . Results . Thirty-one patients were analyzed. BNP and E / E ′ improved, with BNP levels declining from 36.8 ± 30.5   pg / mL to 26.3 ± 25.9   pg / mL (p = 0.0014 ) and E / E ′ dropping from 12.7 ± 4.7 to 11.0 ± 3.3 (p = 0.0376 ). The LVEF showed no significant changes. E / E ′ improved only in patients with E / E ′ ≥ 13.0 . Favorable changes in E / E ′ were canceled when adjusted for body mass index (BMI). Multivariate linear regression analysis revealed that the left ventricular diastolic diameter and ∆ E / E ′ /∆BMI contributed to ∆BNP/baseline BNP (p = 0.0075, R 2 = 0.49264 ). Conclusions . Liraglutide had favorable effects on BNP and E / E ′ but not on LVEF. E / E ′ improvement was only seen in patients with diastolic cardiac function. Body weight reduction affected the change of E / E ′ . The BMI-adjusted E / E ′ significantly contributed to the relative change of BNP. GLP-1 analog treatment could be considered a therapeutic option against diabetic diastolic cardiac dysfunction regardless of body weight. This trial is registered with the University Hospital Medical Information Network in Japan, with clinical trial registration number: UMIN000005565 .